Industrial meaning of university basic research in modern economies - Pohulak-Żołędowska, Elżbieta (Managerial Economics, 2014)
Basic research conducted in the public research institutions are the ones of great importance for both novelty of conduced research and the possibility of their commercial exploiting. Thanks to the institutions which gave the property rights to the publicly produced innovations, it is possible to treat the academic research output as market commodities. It is the next step in the direction of industrial science development. The goal of the article is to show the changes in the approach to the university basic research as a part of the innovation process.